197 Evaluation of a Phytogenic blend and Ractopamine HCl on growth and carcass traits in pigs housed under commercial conditions. (7th December 2018) - Mendoza, S; Gourley, G; Hendel, E; Stelzhammer, S; Mueller, I; Weiland, T; Hunger, C; Murugesan, G
Abstract: The present study aims to evaluate the effect of a phytogenic feed additive (PFA, Digestarom ® Finish, BIOMIN America Inc.) on growth and carcass traits of growing-finishing pigs compared to a control and a ractopamine program. A total of 893 pigs (PIC, BW=23.5 ± 1.1 kg) were allotted to 45 pens (20 ± 1 pigs/pen) and pens were assigned to one of the three dietary treatments (15 pens/treatment). Diets were corn-SBM-DDGs based and fed in four phases to meet the requirements of growing pigs. Dietary treatments consisted of 1) no feed additive [CON], 2) CON + 0.015% PFA, and 3) 5 ppm Ractopamine HCl from d 98 to 119 followed by 7.5 ppm to market [RAC]. Pen BW and feed disappearance were recorded on d 28, 56, 84, 98, 112, and at market (approximately d 122). Individual carcasses (n=883) were assessed to determine the effects of diets. Overall, from d 0 to market, RAC increased (P≤0.033) BW, ADG, and gain:feed, and did not affect ADFI (P=0.666) compared to CON. Pigs fed PFA did not differ from CON or RAC (P≥0.409) on BW, ADG, and ADFI, and had reduced gain:feed compared to RAC (P<0.001) but not different from CON (P=0.646). Pig mortality and pigs removed were not affected by diet (P≥0.653). PFA and RAC increased hot carcass weight (HCW) (P≤0.027) compared to CON. RAC increased (P<0.001) carcass yield, lean percent, and muscle depth compared to CON and PFA. RAC decreased (P≤0.08) fat depth compared to PFA but not different from CON. Pigs fed PFA did not differ on lean percent, muscle depth, and fat depth compared to CON. Ractopamine consistently improved pig growth and carcass traits. Phytogenic blend achieved intermedium performance between the non-feed additive and Ractopamine treatments. More studies are required to investigate the effects of phytogenics in pigs.